Cape Cod. - Thoreau, Henry David (Princeton Classic Editions, 2010)
This new paperback edition of Henry D. Thoreau's compelling account of Cape Cod contains the complete, definitive text of the original. Introduced by American poet and literary critic Robert Pinsky--himself a resident of Cape Cod--this volume contains some of Thoreau's most beautiful writings. In the plants, animals, topography, weather, and people of Cape Cod, Thoreau finds "another world" Encounters with the ocean dominate this book, from the fatal shipwreck of the opening chapter to his later reflections on the Pilgrims' landing and reconnaissance. Along the way, Thoreau relates the experien.